How Knowledge Management Adds Critical Value to E-learning Media - Alrawi, Khalid (Journal of Knowledge Management Practice, 2010)
Media is the combination of text, images, animations, digital library, which is now a standard part of most computer applications. Education media can be a great tool to improve teaching and learning. A growing number of educational institutions (EIs) are developing a new learning culture. It is not just a question of installing a new learning instruments or knowledge management (KM) technologies, it requires a support tools to overcome the difficulties in the selection and evaluation of e-learning process media. Knowledge management and e-learning have much to offer each other, but are not yet integrated in practice. The model presented in this paper is to shed light on the basic concepts of KM and e-learning and a suggestion on how KM and e-learning can be integrated and leveraged for effective online education and training is presented.